TMOD-10. INTRACRANIAL PATIENT-DERIVED XENOGRAFT FROM A PEDIATRIC GLIOBLASTOMA RETAINS MOLECULAR CHARACTERISTICS AND GROWTH PATHWAYS. (31st May 2017) - White, Angela R.; Kumar, Shiva Senthil; Smith, Amanda R.; Ramkissoon, Annmarie; Oatman, Nicole; Dasgupta, Biplab; Breese, Erin H.; Stevenson, Charles; Fuller, Christine; Fouladi, Maryam; DeWire, Mariko D.; Drissi, Rachid; et al.
Abstract: BACKGROUND: Pediatric glioblastomas (pGBM) are characterized by overlapping and unique molecular driver mutations compared to their adult counterparts. Primary cell cultures and patient-derived xenograft (PDX) models of pGBM are rare which may contribute to difficulty in advancing patient outcomes. We have established an orthotopic PDX mouse model from a pGBM resected from a 12 yo male with recurrent disease. The patient received focal radiation and several chemotherapy regimens prior to the recurrence leading to this tumor resection. METHODS: The surgical tumor specimen was dissociated and directly implanted into the brains of immunocompromised (NSG) mice. DNA and immunohistochemical analyses of the patient tumor and PDX were performed. Multiple in vitro culture conditions were tested on the dissociated primary tumor cells and PDX tumor cells. RESULTS: Implantation of the patient tumor cells in mice resulted in tumor growth after 120–250 days. Tumors were serially transplanted successfully. Attempts to establish in vitro cell cultures from primary tumor and from established PDX tumors failed. DNA sequencing of the patient tumor sample and tumors from each PDX generation revealed the H3F3A G34R mutation characteristic of cortical pGBM, and mutations in the TP53, PTEN and PIK3CA genes, all of which were conserved in PDX tumors. Interestingly, the patient tumor showed evidence of telomerase activity and alternative lengthening of telomeres (ALT) as did the PDX tumors. The combined PTEN and PIK3CA mutations in this tumor resulted in activation of the PI3K-mTOR pathway. Treatment of tumor-bearing mice with an mTOR or PI3K inhibitor resulted in suppression of the pathway and reduced proliferation. CONCLUSION: This pGBM PDX model conserved key driver mutations and pathways from the patient tumor. In vitro culture of pGBM can be extremely challenging to establish and more difficult methods such as orthotopic PDX may be required to study these tumors.